Sustainable shipping strategies of Liner companies in this economic downturn - Choo, Sherwin Jian Jia (2017)
The current Liner industry is facing a downturn of unprecedented proportions. The global recession culminating in the ongoing Shipping down cycle, coupled with a glut in vessel supply, have resulted in intensive competitive pressure for Liner companies. More than ever, companies are faced with a tough choice – to make good strategical decisions or risk winding-up. To further elaborate, strategies employed by Liner companies, must tackle the constraints of financial reality whilst balancing the need for business sustainability. As such, an established method of analysing Liner strategies is needed for good decision making. In this regard, our paper seeks to utilised a hybrid Quality Functional Deployment (QFD) model in order to study the impact of customer satisfaction and sustainability on strategical value. Based on past literature, no research has been done on utilising the QFD Model to analyse business strategies employed by Liner companies in the current downturn. The hybrid QFD Model adopted by this paper seeks to systematically analyse Liner strategies. Liner Strategies adopted are also broken down into 3 different fields; Investment & Technology, Operations and Business & Restructuring. The first step of QFD, is to establish the commonalities and objectives within each strategy by clearly identifying key Customer Requirements (CRs), Quality Characteristics (QCs) and Business Strategies (BSs) through existing literature. In the next step, industry consensus via surveys and interviews are conducted to develop a basis for correlation between theory and practice. This correlation is the main function of the QFD model, which derives a valuation of each strategy. Ultimately, this paper seeks to utilise an established systematic approach to determine a ranking detailing the ideal Liner strategies, within each field, and as a whole.